Effects of Myofascial Release Technique on Pain and Disability in Patients with Chronic Lumbar Disc Herniation: A Randomized Trial - Mahbobeh, Samani; Alireza, Motealleh; Soheila, Yazdani; Leila, Abbasi (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2017)
Background Disc herniation is one of the factors that causes low back pain (LBP).Objective This study aimed to evaluate the effect of a myofascial release technique on pain and disability in patients with chronic lumbar disc herniation.Method 30 patients with a herniated lumbar disc, divided into 2 groups. One group (n=15) received electrotherapeutic modalities (TENS, pulsed ultrasound, hot packs) in addition to the myofascial release technique (MFR) on trigger points in 9 soft tissue elements. The other group (n=15) received only electrotherapeutic modalities. All patients underwent 10 treatment sessions. In both groups we assessed back and lower extremity pain intensity, functional disability level and trigger point pain threshold before treatment and after 5 and 10 sessions.Results For back pain, the median between-group differences (95% CI) compared to baseline were 2 (1–2) after the 5th session and 2 (1–4) after the 10th session; the difference between the 5th and 10th sessions was 1 (0–2). For functional disability, the mean between-group differences (95% CI) compared to baseline were 5 points (1.8–8.1) after the 5th session and 8.3 points (4.2–12.3) after the 10th session; the difference between the 5th and tenth sessions was 3.34 points (1.02–5.6). For trigger point pain threshold, the mean between-group differences compared to baseline were −1.47 kg/cm2 (−1.7 to − 1.17) after the 5th session and −3.17 (−3.6 to −2.7) after the 10th session; the difference between the 5th and 10th sessions was −1.7 kg/cm2 (−2.04 to −1.3).Conclusion In conclusion, MFR might be an effective treatment for reducing pain and disability in patients with chronic lumbar disc herniation.
Keywords: myofascial release technique; disc herniation; Trigger points; pain